Management of essential tremor deep brain stimulation-induced side effects - Martinez-Nunez, Alfonso Enrique; Sarmento, Filipe P.; Chandra, Vyshak; Hess, Christopher William; Hilliard, Justin David; Okun, Michael S.; Wong, Joshua K. (Frontiers in Human Neuroscience, 2024)
Deep brain stimulation (DBS) is an effective surgical therapy for carefully selected patients with medication refractory essential tremor (ET). The most popular anatomical targets for ET DBS are the ventral intermedius nucleus (VIM) of the thalamus, the caudal zona incerta (cZI) and the posterior subthalamic area (PSA). Despite extensive knowledge in DBS programming for tremor suppression, it is not uncommon to experience stimulation induced side effects related to DBS therapy. Dysarthria, dysphagia, ataxia, and gait impairment are common stimulation induced side effects from modulation of brain tissue that surround the target of interest. In this review, we explore current evidence about the etiology of stimulation induced side effects in ET DBS and provide several evidence-based strategies to troubleshoot, reprogram and retain tremor suppression.